Larval Fish Assemblage Structure at Coastal Fronts and the Influence of Environmental Variability - Pattrick, Paula; Weidberg, Nicolas; Goschen, Wayne S.; Jackson, Jennifer M.; McQuaid, Christopher D.; Porri, Francesca (Frontiers in Ecology and Evolution, 2021)
Within the coastal zone, oceanographic features, such as fronts, can have major effects on the abundance and distribution of larval fish. We investigated the effects of fronts on larval fish assemblages by jointly collecting physical (ADCP and CTD) and biological (larvae) data in the nearshore waters of the south coast of South Africa, on four separate neap-tide occasions. Accumulation of fish larvae at predominantly internal wave-associated fronts was observed, with higher larval densities inshore of and within the front than farther. On each occasion, larvae of coastal species with pelagic eggs (Mugillidae and Sparidae) were numerically dominant at the front itself, while inshore of the front, larvae of coastal species with benthic eggs (Gobiesocidae and Gobiidae) were more abundant. Offshore catches mainly comprised Engraulidae (pelagic species with pelagic eggs) larvae, which were generally restricted to the bottom, where current velocities were onshore on each occasion. On the occasion when fast (>100cm/s) currents prevailed, however, accumulation of the larvae of coastal species occurred offshore of the front, and larvae were mixed throughout the water column. Thus, larval occurrence at these coastal frontal systems was strongly affected by the degree of mixing by currents, which on most occasions resulted in onshore retention. The results underline the importance of frontal systems in determining the nearshore distributions of fish larvae, particularly by retaining coastal fish species in the inshore region. The environmental variability observed at these frontal systems has potential implications for larval connectivity of fish populations.